Long-Term Outcome of Self Expandable Metal Stents for Biliary Obstruction in Chronic Pancreatitis - Waldthaler, Alexander; Schütte, Kerstin; Weigt, Jochen; Kropf, Siegfried; Malfertheiner, Peter; Kahl, Stefan (JOP. Journal of the Pancreas, 2013)
Context Insertion of a self-expandable metal stent is still controversial for treatment of benign common bile duct stenosis but can be a valuable alternative to surgical treatment. Objective Aim of our study was to analyze the efficacy of covered and uncovered self-expandable metal stent in patients with chronic pancreatitis and common bile duct stenosis. Material and methods Twenty patients with common bile duct stenosis due to alcoholic chronic pancreatitis were retrospective analyzed. All patients had advanced chronic pancreatitis, presenting with calcifications in pancreatic head. Uncovered self-expandable metal stent (uSEMS) were used in 11 patients (3 females, 8 males) while in 9 patients (3 females, 6 males) partially covered self-expandable metal stent (cSEMS) were inserted. All patients treated with self-expandable metal stent had contraindications for surgery. Results Overall mean follow up time was 155 weeks: 206 (52-412) weeks in uSEMS, and 93 (25-233) weeks in cSEMS, respectively. Stent patency was in mean 118 weeks: 159 (44-412) weeks in uSEMS and 67 (25-150) weeks in cSEMS (P=0.019). In the uSEMS group, reintervention was necessary in 5 patients (45%) due to stent obstruction, whereas in the cSEMS group 4 patients (44%) needed reintervention (2 obstructions, 2 migration). Stent migration is an early complication, compared to obstruction (P<0.05), and in cSEMS obstruction occurred significantly earlier compared to uSEMS (P<0.05). Conclusion Patency of uSEMS was significantly longer compared to partially cSEMS. Available self-expandable metal stent, unfortunately, do not meet the demands on successful treatment of benign common bile duct stenosis. Image: Kaplan-Meier-plot of estimated stent patency.